Highly stretchable and durable fibrous strain sensor with growth ring-like spiral structure for wearable electronics. (15th November 2021) - Kong, Wei-Wei; Zhou, Chang-Ge; Dai, Kun; Jia, Li-Chuan; Yan, Ding-Xiang; Li, Zhong-Ming
Abstract: Wearable strain sensors promote various emerging intelligent fields. Compared with the planar strain sensors, fibrous strain sensors are highly desirable for practical applications because they are favour of conformably attaching onto uneven surfaces and integrating into regular fabrics. Herein, inspired by the growth ring of tree, a highly stretchable silver nanowire/polydimethylsiloxane based fibrous strain sensor with spiral structure was innovatively prepared by cost-efficient coating plus rolling up technique. This unique spiral structure endowed the fibrous strain sensor with wide sensing range of 100% strain, outstanding linearity, gauge factor of 3.0, negligible hysteresis, and excellent reliability. Thanks to these superior characteristics, our sensor can not only accurately detect human movements when being attached to joints directly or woven in a cotton glove but also control the brightness of bulb when being connected into a circuit, showing great potential for wearable sensing electronics and next-generation circuit control elements. This work paves a promising way for the development of high-performance fibrous strain sensor. Graphical abstract: Image 1 Highlights: A stretchable AgNW/PDMS based fibrous strain sensor with growth ring-like spiral structure was prepared. The sensor possesses wide sensing range, outstanding linearity, negligible hysteresis, and excellent durability. The sensor can accurately detect human movements when being attached to joints directly or woven in a cotton glove. The sensor can serve as a next-generation circuit control element.